ANALISIS PENGARUH KEPUASAN PENGGUNA PUBLIC COMPUTER TERHADAP EFISIENSI DAN EFEKTIFITAS MAHASISWA TRISAKTI SCHOOL OF MANAGEMENT - DICKY SUPRIATNA; TJHAI FUNG JIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
The purpose of this study is to examine the influence of public computer users' satisfaction toward the efficiency and effectiviness of students at Trisakti school of management. User satisfaction was measured by feature completeness, stability/ accuracy, user friendly, innovation, security and flexibility. This study uses 380 respondents which are students at Trisakti School of Management. Data was collected by using simple random sampling. Using Multiple Regression Analysis, the result shows that public computer users satisfaction have significant influence toward efficiency and effectiviness of students at Trisakti School of Management. ilowever, from t-test shows that feature completeness, innovation, security, flexibility have significant influence toward efficiency, and feature completeness, innovation have significant influence toward effectiveness.